(untitled) (Research, Society and Development, 2020)
Pregnancy is a period when a woman is vulnerable due to changes that occur in her body. The nutritional status in the preconceptional period is a determining factor for embryonic development. The objective of this study is to assess food insecurity and its associated factors in pregnant adolescents seen in primary care. This is a quantitative cross-sectional study, as it takes objectivity into account, enabling the measurement of its results through the analysis of data and statistical tools. A sample of 185 pregnant teenagers attended at the basic health units in Caxias-MA. Among the interviewees, 157 (84.9%) are aged between 15 and 17 years. As for education, only 21 (11.4%) said they had completed high school. Of the 185 adolescents, 14 (7.6%) reported having planned the pregnancy, while 171 (92.4%) said the pregnancy was unwanted. As for nutritional status, 29 (50.8%) had grade I obesity and 1 (1.8%) is in the grade III obesity category. Regarding AI, 80 (43.2%) are on the moderate scale and 38 (20.5%) on the severe scale. It is concluded that AI increases the chances of nutritional disorders, excessive weight gain or loss, predisposition to chronic comorbidities, among other unfavorable situations.